Ordered mesoporous phenolic resins: Highly versatile and ultra stable support materials - Muylaert, Ilke; Verberckmoes, An; De Decker, Jeroen; Van Der Voort, Pascal (Advances in colloid and interface science, 2012)
Ordered mesoporous phenolic resins and carbons – an advanced class of ultra-stable mesoporous materials – offer potential applications in the field of catalysis, electrodes and adsorbents. This review gives an extensive overview of the main principles and the recent progress made in the synthesis of these innovative materials using the soft-template method. Furthermore, the versatility towards functionalization and the incorporation of hetero-atoms in the organic framework of the mesoporous resins and carbons are considered. Finally, the broad range of potential applications is discussed and future perspectives in the field of mesoporous polymers and carbons are given. ► Main synthesis principles of phenolic resins using the soft-template method. ► Thermally and mechanically stable support materials. ► Functionalization and incorporation of metals in mesoporous resins and carbons. ► Versatile use in catalysis, adsorption and electrochemistry.